Random copolymerization sulfonated benzene-substituted polyphenyl ionomer material for fuel cell and preparation method of random copolymerization sulfonated benzene-substituted polyphenyl ionomer material
Through the preparation of random copolymerized sulfonated benzene polyphenyl ionomer material, the problems of low conductivity and poor chemical stability of the proton exchange membrane are solved, and efficient proton conduction and good chemical stability are achieved.
Patent Information
- Application Number
- CN202510092236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing proton exchange membrane has low conductivity and poor chemical stability.
A random copolymerized sulfonated benzene polyphenyl ionomer material was used to prepare a high molecular weight proton exchange membrane material by mixing monomer I, monomer III, catalyst, alkaline regulator and solvent for coupling reaction.
It achieves high proton conductivity and high chemical stability, and improves the performance and durability of fuel cells.
Smart Images

Figure CN119859249A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membrane materials for fuel cells, and in particular relates to an ionomer. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) can convert chemical energy into electrical energy. They are widely used as clean and efficient energy conversion devices because of their high conversion efficiency and fast startup. Currently, the widely used perfluorosulfonic acid (PFSA) polymer membranes (such as Nafion and Gore Select) are most commonly used as electrolytes. They have high proton conductivity and excellent mechanical properties, but they also have some technical problems such as high gas permeability, limited operating temperature, and complex manufacturing process. In response to the problems of perfluorosulfonic acid proton exchange membranes, current research is mainly focused on improving existing perfluorosulfonic acid proton exchange membranes and developing new non-fluorinated proton exchange membrane materials. Sulfonated benzene-substituted polyphenyl PEM has the advantages of good thermal stability and low gas permeability, and is expected to become a new proton exchange membrane material.
[0003] Ionomer refers to a polymer containing ionic groups in the hydrocarbon molecular chain. The ionic groups can form a cross-linked network through ionic interactions, so it has many unique and excellent properties. At present, sulfonated benzene-substituted polyphenylene ionomer membrane materials are widely studied. Holdcroft et al. reported that sulfonated benzene-substituted polyphenylene ionomers showed very high thermal oxidation stability and good dimensional stability. Miyatake successfully synthesized a series of new sulfonated polyphenylene ionomers (SPP-BP) containing sulfonated p-phenylene and unsubstituted p-biphenylene and m-biphenylene through Ni(0)-promoted coupling reactions. The SPP-BP membrane exhibited high proton conductivity, mechanical strength and chemical stability. This preparation method has the characteristics of simple synthesis, high molecular weight of the obtained ionomer, and easy regulation. Patent Publication No. CN117304452A discloses a sulfonated polyphenylene ionomer and a preparation method thereof and a proton exchange membrane. The preparation method of the sulfonated polyphenylene ionomer is to dissolve the polymer in a solvent as monomers I, II and III, and promote the occurrence of coupling reaction between monomers by Ni (0) catalysis under alkaline conditions, and obtain the copolymer through precipitation, separation and drying. The exchange membrane is made into a high proton conductivity and low permeability in the accelerated durability test of the running fuel cell. Although a series of sulfonated benzene-substituted polyphenyl ionomers are disclosed in the prior art, the influence of different ionomer structures on performance needs to be further explored, and the ionomer proton exchange membrane still has problems such as low conductivity and poor chemical stability. Summary of the invention
[0004] In view of the technical problems of low conductivity and poor chemical stability of proton exchange membranes, the present invention provides a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material and a preparation method thereof. The proton exchange membrane material prepared from the ionomer exhibits high proton conductivity and high chemical stability.
[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0006] A random copolymer sulfonated benzene-substituted polyphenyl ionomer material for fuel cells, the structural formula is:
[0007]
[0008] Where R is R1, R2, R3, R4, R5, R6 are independently selected from H, F, -(CF2) x At least one of CF3, -CF3 and phenyl, n1 is an integer of 0-10, n2 is an integer of 0-12, x is an integer of 0-15; m:n is 1:(0-99).
[0009] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps: mixing monomer I, monomer III, a catalyst, an alkaline regulator and a solvent to obtain a reaction solution and performing a coupling reaction, and obtaining a target ionomer after the reaction is completed; the structural formulas of the monomer I and the monomer II are as follows:
[0010] Wherein X is Cl or Br or I, and R is selected from:
[0011] One of, R1, R2, R3, R4, R5, R6 are independently selected from H, F, -(CF2) x At least one of CF3, -CF3 and phenyl, n1 is an integer of 0-10, n2 is an integer of 0-12, and x is an integer of 0-15.
[0012] The molar ratio of the monomer I to the monomer II is 1:(0-99); the concentration of the monomer I in the reaction solution is 0.04-0.7 mmol / mL.
[0013] The solvent is any one of N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO) or N-methylpyrrolidone (NMP).
[0014] The alkaline regulator is any one or more of K2CO3, Na2CO3, LiOH, NaOH or KOH; the molar ratio of monomer I to the alkaline regulator is 1:(1-20).
[0015] The catalyst comprises a Ni(0) catalyst and a ligand, wherein the Ni(0) catalyst is one of Ni(COD)2, Ni(CDT), Ni(OAc)2, NiBr2 / Zn, NiCl2 / Zn, and NiI2 / Zn; the ligand is 2,2'-bipyridine, and the molar ratio of the total molar number of monomer I and monomer II to the Ni(0) catalyst is 1:(1-6).
[0016] The molar ratio of Ni(0) to 2,2'-bipyridine is 1:(0.2-5).
[0017] The coupling reaction temperature is 50-100° C., and the reaction time is 2-24 h.
[0018] After the reaction is completed, the reaction solution is added to a precipitant, the precipitate is separated out and filtered, and then the precipitate is washed and dried to obtain the target ionomer.
[0019] The precipitant is an acidic aqueous solution; the acidic aqueous solution is a hydrochloric acid or sulfuric acid aqueous solution; the concentration of the acidic aqueous solution is 4-6 mol / L.
[0020] The invention has the following beneficial effects: the invention has the advantages of simple synthesis, low cost, high molecular weight of the obtained polymer, good conductivity of the proton exchange membrane, high water absorption, etc.; at the same time, the invention introduces an alkyl chain or a small molecule benzene ring segment (monomer II) on the basis of the sulfonated phenyl polyphenyl, which is mainly used to improve the mechanical properties of the sulfonated phenyl polyphenyl membrane material, and the prepared proton exchange membrane has broad application prospects when used as a proton exchange membrane of a hydrogen fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 (a) of SPP-BAF obtained in Example 1 1 HNMR, (b) 19 F NMR spectrum.
[0023] Figure 2 This is the Fourier infrared spectrum of the SPP-BAF film prepared in Example 1.
[0024] Figure 3 is the electrical conductivity of the SPP-BAF membrane prepared in Example 1.
[0025] Figure 4is the water absorption rate of the SPP-BAF membrane prepared in Example 1.
[0026] Figure 5 (a) of SPP-PAF prepared in Example 4 1 H NMR, (b) 19 F NMR spectrum.
[0027] Figure 6 This is the Fourier infrared spectrum of the SPP-PAF film prepared in Example 4.
[0028] Figure 7 The conductivity of the SPP-PAF membrane prepared in Example 4.
[0029] Figure 8 It is the water absorption rate of the SPP-PAF film prepared in Example 4. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The monomer I used in Examples 1, 3, 4, 7, and 10 is:
[0032] The monomer I used in Examples 2, 5 and 9 is: The monomer I used in Examples 6 and 8 is:
[0033] Example 1
[0034] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0035] Monomer I (0.4899 g), 2,2-bis(4-chlorophenyl)hexafluoropropane (0.0653 g), K2CO3 (0.0498 g), 2,2'-bipyridine (0.3115 g), and DMSO (4.7 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 160 ° C for 2 hours using a Dean Stark water separator under N2. After azeotropic dehydration, the mixture was cooled to 80 ° C. Ni(COD)2 (0.5225 g) was added to the mixture. After reacting at 80 ° C for 3 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer (SPP-BAF) was obtained by drying overnight at 80 ° C in a vacuum oven.
[0036] Preparation of proton exchange membrane: The SPP-BAF obtained in Example 1 was dissolved in DMSO to prepare a solution with a mass fraction of 3%, filtered and cast on a glass plate, heated to remove the membrane, immersed in a hydrochloric acid aqueous solution, washed with deionized water until neutral, and dried to obtain a proton exchange membrane.
[0037] Figure 1 is the NMR spectrum of SPP-BAF prepared in Example 1, Figure 1 (a): 1 H NMR: The peak at 6.0-8.0 ppm in the aromatic region is the H proton on the phenylated polyphenylene. Figure 1 (b) 19 F NMR has a group of peaks at -63ppm, corresponding to the F of -CF3, and infrared spectroscopy further proves the polymer structure ( Figure 2 ), several characteristic absorption peaks were observed in the FT-IR spectrum, (1120, 1004, 634 cm -1 ) is the absorption peak of sulfonic acid group, 705cm -1 The absorption peak generated by -CF3 proves the successful preparation of SPP-BAF series membranes.
[0038] The molecular weight of SPP-BAF prepared in Example 1 was measured by GPC (Table 1), M n =59.8 kDa, M w =206.3 kDa, M w / M n =3.45.
[0039] Table 1
[0040] Membrane <![CDATA[M n (kDa)]]> <![CDATA[M w (kDa)]]> <![CDATA[M w / M n ]]> SPP-BAF 59.8 206.3 3.45
[0041] Proton conductivity test: The proton conductivity of the proton exchange membrane in the in-plane direction was measured using the AC impedance method and compared with that of the Nafion 211 membrane. Figure 3As shown in the figure, it can be seen that the molecular weight of SPP-BAF membrane is higher than that of Nafion 211 membrane in the test range, and at 80°C and 100% RH, the proton conductivity of SPP-BAF is: 460.82 mS cm -1 .
[0042] Water absorption test: The water absorption of the SPP-BAF membrane prepared in Example 1 was tested at different temperatures in a fully hydrated state. The water absorption of the SPP-BAF membrane was tested at different temperatures within the test range ( Figure 4 ), the water absorption rate of SPP-BAF membrane is higher than that of Nafion membrane, and the water absorption rate of SPP-BAF membrane is 4 times that of Nafion membrane at 80℃.
[0043] The SPP-BAF prepared in Example 1 was applied to a fuel cell. At 80°C, 100% RH, H2 / Air, the maximum power density of the fuel cell was 0.535 W cm -2 .
[0044] Example 2
[0045] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0046] Monomer I (0.6457 g), 4,4'-dibromo-1,1'-biphenyl (0.1357 g), K2CO3 (0.0622 g), 2,2'-bipyridine (0.5312 g), and DMSO (8.0 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 160°C for 2 hours using a Dean Stark water separator under N2. After azeotropic dehydration, the mixture was cooled to 80°C. Ni(COD)2 (1.2728 g) was added to the mixture. After reacting at 80°C for 4 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer was obtained by drying overnight at 80°C in a vacuum oven.
[0047] Example 3
[0048] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0049] Monomer I (0.6124 g), 4,4"-dichloro-3,3"-bis(trifluoromethyl)-1,1':4',1"-terphenyl (0.0789 g), KOH (0.0252 g), 2,2'-bipyridine (0.3649 g), and DMSO (7.6 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 150°C for 3 hours using a Dean Stark water trap under N2. After azeotropic dehydration, the mixture was cooled to 80°C. Ni(COD)2 (0.6121 g) was added to the mixture. After reacting at 80°C for 4 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer (SPP-TPF) was obtained by drying at 80°C overnight in a vacuum oven.
[0050] Preparation of proton exchange membrane: The SPP-TPF obtained in Example 3 was dissolved in DMAc to prepare a solution with a mass fraction of 3%, filtered and cast on a glass plate, heated to remove the membrane, immersed in a hydrochloric acid aqueous solution, washed with deionized water until neutral, and dried to obtain a proton exchange membrane.
[0051] The SPP-TPF obtained in Example 3 was tested by nuclear magnetic resonance. 1 H NMR: The peak at 6.0-8.0 ppm in the aromatic region is the H proton on the phenylated polyphenylene. 19 F NMR has a group of peaks at -60.60 ppm, corresponding to the F of -CF3.
[0052] Proton conductivity test: The proton conductivity of the proton exchange membrane in the in-plane direction was measured by AC impedance method. At 80°C and 100% RH, the proton conductivity of SPP-TPF was: 157.45mS cm -1 .
[0053] The SPP-TPF prepared in Example 3 was applied to a fuel cell. At 80°C and 100% RH, the maximum power density of the fuel cell was 0.554 W cm -2 .
[0054] Example 4
[0055] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0056] Monomer I (0.6124 g), 3,3'-(perfluorohexane-1,6-diyl)bis(chlorobenzene) (0.0764 g), Na2CO3 (0.0477 g), 2,2'-bipyridine (0.3418 g), and DMAc (4.2 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 170°C for 2 hours using a Dean Stark water separator under N2. After azeotropic dehydration, the mixture was cooled to 80°C. Ni(OAc)2 (0.3440 g) was added to the mixture. After reacting at 80°C for 3.5 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer (SPP-PAF) was obtained by drying overnight at 80°C in a vacuum oven.
[0057] Preparation of proton exchange membrane: The SPP-PAF obtained in Example 4 was dissolved in DMSO to prepare a solution with a mass fraction of 3%, filtered and cast on a glass plate, heated to remove the membrane, immersed in a hydrochloric acid aqueous solution, washed with deionized water until neutral, and dried to obtain a proton exchange membrane.
[0058] Figure 5 is the NMR spectrum of SPP-PAF prepared in Example 4, Figure 5 (a): 1 H NMR: The peaks at 6.0-8.2 ppm in the aromatic region are H protons on the phenylated polyphenylene. Figure 5 (b): 19 F NMR has three peaks at -109, -121, and -121.9 ppm, corresponding to three types of -CF2 F. Infrared spectroscopy was used to further prove the polymer structure ( Figure 6 ), several characteristic absorption peaks were observed in the FT-IR spectrum, (1140, 996, 637 cm -1 ) is the absorption peak of sulfonic acid group, 751cm -1 The absorption peak produced by -CF2 proves the successful preparation of SPP-PAF series membranes.
[0059] The molecular weight of SPP-PAF prepared in Example 4 was measured by GPC (Table 2), M n =37.1 kDa, M w =150.0 kDa, M w / M n =4.04.
[0060] Table 2
[0061] Membrane <![CDATA[M n (kDa)]]> <![CDATA[M w (kDa)]]> <![CDATA[M w / M n ]]> SPP-PAF 37.1 150.0 4.04
[0062] Proton conductivity test: The proton conductivity of the proton exchange membrane in the in-plane direction was measured using the AC impedance method and compared with that of the Nafion 211 membrane. Figure 7 As shown in Figure 2, the conductivity of SPP-PAF is comparable to that of Nafion 211 membrane, and at 80 °C and 100% RH, the proton conductivity of SPP-PAF is: 145.23 mS cm -1 .
[0063] Water absorption test: The water absorption of the SPP-PAF film prepared in Example 4 was tested at different temperatures in a fully hydrated state. The water absorption of the SPP-PAF film was tested at different temperatures ( Figure 8 ), the water absorption rate is higher than that of Nafion membrane, and the water absorption rate of SP P-PAF membrane is twice that of Nafion membrane at 80℃.
[0064] The SPP-PAF prepared in Example 4 was applied to a fuel cell. At 80°C and 100% RH, the maximum power density of the fuel cell was 0.515 W cm -2 .
[0065] Example 5
[0066] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0067] Monomer I (0.4899 g), NaOH (0.0137 g), 2,2'-bipyridine (0.1866 g), and NMP (3 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 170°C for 2.5 hours using a Dean Stark water trap under N2. After azeotropic dehydration, the mixture was cooled to 80°C. Ni(OAc)2 (0.3130 g) was added to the mixture. After reacting at 80°C for 3 hours, the mixture was poured into a large excess of 4M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. Copolymers (SPPs) were obtained by drying overnight at 80°C in a vacuum oven.
[0068] Preparation of proton exchange membrane: The SPPs obtained in Example 5 were dissolved in DMAc to prepare a solution with a mass fraction of 3%, filtered and cast on a glass plate, heated to remove the membrane, immersed in a hydrochloric acid aqueous solution, washed with deionized water until neutral, and dried to obtain a proton exchange membrane.
[0069] The SPPs obtained in Example 5 were tested by NMR. 1 H NMR: The peak at 6.0-8.0 ppm in the aromatic region is the H proton on the phenylated polyphenylene.
[0070] Proton conductivity test: The proton conductivity of the proton exchange membrane in the in-plane direction was measured by AC impedance method. At 80°C and 100% RH, the proton conductivity of SPPs was: 151mS cm -1 .
[0071] The SPPs prepared in Example 5 were applied to a fuel cell. At 80°C, 100% RH, H2 / Air, the maximum power density of the fuel cell was 0.526 W cm -2 .
[0072] Example 6
[0073] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0074] Monomer I (0.6810 g), 3,3'-(perfluorobutane-1,4-diyl)bis(iodobenzene) (0.1138 g), K2CO3 (0.0622 g), 2,2'-bipyridine (0.3691 g), and DMSO (5.6 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 160° C. for 2 hours using a Dean Stark water trap under N2. After azeotropic dehydration, the mixture was cooled to 80° C. Ni(COD)2 (2.6534 g) was added to the mixture. After reacting at 80° C. for 4 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer was obtained by drying overnight at 80° C. in a vacuum oven.
[0075] Example 7
[0076] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0077] Monomer I (0.9798 g), 1,6-bis(3-chlorophenyl)hexane (0.1374 g), Na2CO3 (0.0763 g), 2,2'-bipyridine (0.3271 g), and DMAc (10.4 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 170° C. for 2 hours using a Dean Stark water separator under N2. After azeotropic dehydration, the mixture was cooled to 80° C. Ni(OAc)2 (4.9382 g) was added to the mixture. After reacting at 80° C. for 3.5 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer was obtained by drying overnight at 80° C. in a vacuum oven.
[0078] Example 8
[0079] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0080] Monomer I (0.2043 g), 3,3'-(perfluorobutane-1,4-diyl)bis(iodobenzene) (0.6650 g), K2CO3 (0.3110 g), 2,2'-bipyridine (11.9443 g), and DMSO (12.7 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 160° C. for 2 hours using a Dean Stark water trap under N2. After azeotropic dehydration, the mixture was cooled to 80° C. Ni(COD)2 (6.0103 g) was added to the mixture. After reacting at 80° C. for 4 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer was obtained by drying overnight at 80° C. in a vacuum oven.
[0081] Example 9
[0082] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0083] Monomer I (0.6457 g), 4,4'-dibromo-1,1'-biphenyl (0.1357 g), K2CO3 (0.0622 g), 2,2'-bipyridine (0.5312 g), and DMSO (8.0 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 160°C for 2 hours using a Dean Stark water separator under N2. After azeotropic dehydration, the mixture was cooled to 80°C. Ni(COD)2 (1.2728 g) was added to the mixture. After reacting at 80°C for 4 hours, the mixture was poured into a large excess of 6M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer was obtained by drying overnight at 80°C in a vacuum oven.
[0084] Example 10
[0085] A method for preparing a random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell comprises the following steps:
[0086] Monomer I (0.9798 g), 1,6-bis(3-chlorophenyl)hexane (0.003 g), Na2CO3 (0.0763 g), 2,2'-bipyridine (0.3271 g), and DMAc (1 mL) were added to a 100 mL three-necked flask. The mixture was heated in a temperature-controlled oil bath at 170° C. for 2 hours using a Dean Stark water separator under N2. After azeotropic dehydration, the mixture was cooled to 80° C. Ni(OAc)2 (4.9382 g) was added to the mixture. After reacting at 100° C. for 1 hour, the mixture was poured into a large excess of 4M HCl to precipitate the product. The crude product was washed several times with concentrated HCl and deionized water. The copolymer was obtained by drying overnight at 80° C. in a vacuum oven.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A random copolymer sulfonated benzene-substituted polyphenyl ionomer material for a fuel cell, characterized in that: The structural formula is: Where R is R1, R2, R3, R4, R5, R6 are independently selected from H, F, -(CF2) x At least one of CF3, -CF3 and phenyl, n1 is an integer of 0-10, n2 is an integer of 0-12, and x is an integer of 0-15; m:n is 1:(0-99).
2. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 1, characterized in that: The method comprises the following steps: mixing monomer I, monomer II, a catalyst, an alkaline regulator and a solvent to obtain a reaction solution and performing a coupling reaction, and obtaining a target ionomer after the reaction is completed; the structural formulas of the monomer I and the monomer II are as follows: Where X is Cl, Br or I, R is R1, R2, R3, R4, R5, R6 are independently selected from H, F, -(CF2) x At least one of CF3, -CF3 and phenyl, n1 is an integer of 0-10, n2 is an integer of 0-12, and x is an integer of 0-15.
3. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The molar ratio of the monomer I to the monomer II is 1:(0-99); the concentration of the monomer I in the reaction solution is 0.04-0.7 mmol / mL.
4. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The solvent is any one of N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone.
5. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The alkaline regulator is any one or more of K2CO3, Na2CO3, LiOH, NaOH or KOH; the molar ratio of monomer I to the alkaline regulator is 1:(1-20).
6. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The catalyst comprises a Ni(0) catalyst and a ligand in a molar ratio of 1:(0.2-5), wherein the Ni(0) catalyst is one of Ni(COD)2, Ni(CDT), Ni(OAc)2, NiBr2 / Zn, NiCl2 / Zn, and NiI2 / Zn; and the ligand is 2,2'-bipyridine.
7. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The molar ratio of the total molar number of the monomer I and the monomer II to the Ni(0) catalyst is 1:(1-6).
8. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The coupling reaction temperature is 50-100° C., and the reaction time is 2-24 h.
9. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: After the reaction is completed, the reaction solution is added to a precipitant, the precipitate is separated out and filtered, and then the precipitate is washed and dried to obtain the target ionomer.
10. The method for preparing the random copolymerized sulfonated benzene-substituted polyphenyl ionomer material for fuel cells according to claim 2, characterized in that: The precipitant is an acidic aqueous solution; the acidic aqueous solution is a hydrochloric acid or sulfuric acid aqueous solution; the concentration of the acidic aqueous solution is 4-6 mol / L.
Citation Information
Patent Citations
Sulfonated polyphenylene ionomer, preparation method thereof and proton exchange membrane
CN117304452A
Polyphenylenes, methods, and uses thereof
CN110730774A
Main chain torsion type sulfonated polyphenylene ionomer, preparation method thereof and proton exchange membrane
CN117343287A
Ion-conducting sulfonated polymeric materials
WO2002025764A1
Sulfonated benzene polyphenyl ionomer and method for preparing same, and proton exchange membrane
WO2023185149A1
Cited By
Fuel cell membrane electrode and preparation method thereof
CN120613416A
High-performance membrane electrode based on platinum-carbon catalyst and preparation method thereof
CN120637512A
Trifluoromethyl functionalized sulfonated benzene-substituted polyphenyl polymer as well as preparation method and application thereof
CN121181853A